Web-based computerized adaptive testing system for mathematics - Ng, Chiun Cher. (2010)
The usage of the Internet is becoming more common nowadays, and most of the systems are usually targeted at interests and browsing behaviors instead of taking into account the learning ability of the users, which proves to be one important factor in the society today. The main objective of this project is to develop a web-based assessment system for mathematics based on past year examination questions such as undergraduate mathematics questions. The system, using Computerized Adaptive Testing (CAT), will allow the users to browse, search and test their individual ability or achievements by administering a simulated test based on past examination questions from a pre-calibrated item bank. Computerized Adaptive Testing (CAT) has taken its place and currently, is determined to be the most cost and time effective way to assess the potential of its users. Compared to traditional tests and examinations, CAT is more superior as it tends to yield more accurate results. In conclusion, CAT is a far more efficient technology as it is able to assess the ability of the users in a lesser time, by asking them less number of questions.